Cyberspace: rethinking the metaphor of the human - Fonseca González, Vanessa (2003)
In this paper the author refers to changes of perception to be addressed and like in other historical moments, a change of metaphor that must not be understood only as a change cosmetological. That is, each extension of the senses changes the way of thinking, acting and a way of perceiving the world; this in turn implies a change in the process of knowledge. In this way, the author ends rethinking that humanism on the threshold of the twenty-first century, is probably one of the most frigid from the end of the century.